Managing Innovation in European Research Projects - Estil-les, Maria del Cacho; Fanti, Maria Pia; Ukovich, Walter (International Journal of Business Management and Finance Research, 2025)
This paper presents a new innovation management approach in research projects. Based on the transformation from Open Innovation to User-Centric Innovation, going through Networked Innovation, the starting point of the proposed innovation process is the investigation of the users and stakeholders needs. In the presented approach, users and innovators exchange information to satisfy stakeholders needs. In order to meet these requirements, innovators develop Innovation Tools (Its) as a result of innovation activities. The concept of “Innovation Tools” is introduced as the mean to meet users’ needs and objectives. As a result of the study, a new innovation management strategy is defined. The defined strategy can be applied in European founded research projects. The originality of the presented work is the introduction of the novel innovation management approach called “European Project User-Centric Innovation” (EP U-CI), that can be applied in European founded research projects. The value of the EP U-CI strategy is enlightened by the application to the Horizon Europe IN2CCAM project and consists in the centrality of the users needs and in the way stakeholders interact with the innovators.